Effect of social determinants on health: Racism on cardiovascular disease - Nuñez Delgado, Rocio del Pilar (2023)
The high morbidity and mortality from Cardiovascular Disease (CVD), reaffirms it as a public health problem worldwide; The classic cardiovascular risk factors are well known, such as: Hypertension, diabetes, dyslipidemia, tobacco. And the non-classical ones, such as Social determinants of health (DSS) and racism; that play a fundamental role. Through the present narrative review, updated literature is detailed about how DSS exert influence and its pathophysiology in CVD. In the period of one year, 10 articles that met inclusion criteria whose theme is: DSS, racism and CVD were selected. It concludes that the DSS and racism play a major role for the generation, evolution, and even fatal outcome of different cardiovascular diseases; whose influence worsened by the COVID-19 pandemic.